Verbal autopsy analysis of maternal mortality in Bong County, Liberia: a retrospective mixed methods study - Jody R Lori; Haeun Lee; Joseph Perosky; Madison Horton; Christopher Reynolds; Aloysius Nyanplu (BMJ Open Quality)
Background While the medical contributors to maternal mortality are well known, the contextual contributors are less known and understudied. Liberia has one of the highest maternal mortality rates in sub-Saharan Africa, with recent increases in maternal deaths in rural Bong County. The purpose of this study was to better classify the contextual factors leading up to maternal deaths and to develop a list of recommendations to prevent future similar deaths.Methods A retrospective mixed method study was conducted examining 35 maternal deaths in Bong County, Liberia using verbal autopsy reports from 2019. An interdisciplinary death audit team reviewed and analysed the maternal deaths to determine the contextual causes of the maternal death.Findings This study identified three contextual causes: limited resources (materials, transportation, facility, staff), inadequate skills and knowledge (staff, community, family, patient), and ineffective communication (between providers, between health facilities and hospitals, and between provider and patient/family). Of these, inadequate patient education (54.28%), inadequate staff education and training (51.42%), ineffective communication between health facilities and hospitals (31.42%), and inadequate materials (28.57%) were most frequently mentioned.Conclusion Maternal mortality remains an issue in Bong County, Liberia, due to addressable contextual causes. Interventions to ameliorate these preventable deaths include ensuring availability of resources and transportation through improved supply chain and health system accountability. Recurring training should be provided to healthcare workers which involves husbands, families and communities. Innovative means for providers and facilities to communicate clearly and consistently should also be prioritised to prevent future maternal deaths in Bong County, Liberia.